Thin Film Catalysts: Ni5P4 (Cathodic) and LiCoO2 (Anodic) for Electrolysis of Water. (1st August 2016) - Hwang, Shinjae; Porter, Spencer H; Gardner, Graeme; Laursen, Anders B.; Wang, Hao; Li, Mengjun; Amarasinghe, Voshadhi; Taghaddos, Elaheh; Safari, Ahmad; Garfunkel, Eric; Greenblatt, Martha; Dismukes, Gerard Charles
Abstract : Inexpensive earth-abundant catalysts are required to accelerate both the oxidative and reductive half reactions for electrolysis of water. Using natural enzymes as models, such as the CaMn4 O5 cubane motif in the water oxidizing complex of photosystem II and the Ni-S active site of Ni-Fe hydrogenase, we previously developed cubic LiCoO2 and nickel phosphides that mimic their chemistry, respectively. Here we prepared thin films of spinel – LiCo2 O4, for the (water oxidation) oxygen evolving reaction (OER), and Ni5 P4, for the hydrogen evolving reaction (HER) on Au substrates. We investigated their atomic structure (PXRD), Raman vibrational modes, surface morphology (SEM, AFM), core electronic levels (XPS), and electrochemical catalytic performance. These non-precious metal thin film materials function as well as the individual nanocrystalline particles and are expected to be applicable to use in monolithic photoelectrochemical cells and potentially fuel cells.